Economic Diplomacy through International Tourism Co-operation : the Case of South Africa and China, 2009 to 2017 - Zondi, Siphamandla (University of Pretoria, 2018)
Mini Dissertation (MA Diplomatic Studies)--University of Pretoria, 2017.